Diversity of small carnivores in Pendjari biosphere reserve, Benin - SOGBOHOSSOU, ETOTEPE A.; AGLISSI, Janvier (My University, 2017)
Small carnivores, important members of ecosystems are poorly studied in Africa. In order to fill this gap, we camera trapped 103 sites in Pendjari Biosphere Reserve, West Africa. The specific objectives were to assess the species richness in the small carnivore guild and whether the land use system affect this diversity. For a total trapping effort of 3607 days between November 2014 and April 2015, we got 543 independent captures of at least ten species. The trapping success of small carnivores was 15 pictures/100 days in the reserve. Small carnivores were found in 68% of the sites. Jackal and genet were the most abundant distributed species in the park while mongooses and genets were more common in hunting zones. Hunting zones being more prone to human disturbance, our results suggested that Felidae were more vulnerable to anthropogenic activities than other carnivores. These species and jackal could be used as indicator species in Pendjari ecosystem. Conservation efforts should be improved, especially in hunting zones, to guaranty the survival of small carnivores in this ecosystem.
Keywords: Small mammals; species richness; camera trapping; West Africa